FREQUENCY OF DYSLIPIDEMIA IN PAKISTANI SOLDIERS IN MULTAN GARRISON: Frequency of Dyslipidemia - Iqbal, Javed; Rehman, Muhammad Atiq Ur; Mehmood, Sarfraz; Irshad, Tariq Mehmood (Pakistan Armed Forces Medical Journal, 2009)
Objective:   To determine the frequency of dyslipidemia in army soldiers in Multan garrison. Study Design:  Descriptive study. Place and Duration of Study:  Department of Medicine at Combined Military Hospital Multan from January 1998 to January 2000. Subject and Methods: One thousand, otherwise healthy male soldiers, from various units in Multan Garrison were included in this study. Their fasting venous blood samples were obtained in sterile disposable syringe for lipid profile test.  Those who were smokers or had history of diabetes mellitus, hypothyroidism or family history of early coronary heart disease (CHD) were excluded.  Results: Sixty eight (6.8%) soldiers were found to have dyslipidemia. Thirty (3%) had low HDL levels, 26 (2.6%) had increased serum triglyceride levels, 10 (1.0%) soldiers were found having  isolated increase in LDL-cholesterol level with normal  total serum cholesterol, and 2(0.2%) were having raised total and LDL cholesterol levels. Eighty four percent of studied population was not aware of the fact that dyslipidemia is a risk factor for heart disease. Conclusion: Frequency of dyslipidemia in Pakistani soldiers is moderate and it can be further reduced by increasing the awareness of disease.